Isoform-selective decrease of glycogen synthase kinase-3-beta (GSK-3β) reduces synaptic tau phosphorylation, transcellular spreading, and aggregation - Amaral, Ana Claudia (iScience, 2021)
It has been suggested that aberrant activation of glycogen synthase kinase-3-beta (GSK-3β) can trigger abnormal tau hyperphosphorylation and aggregation, which ultimately leads to neuronal/synaptic damage and impaired cognition in Alzheimer disease (AD). We examined if isoform-selective partial reduction of GSK-3β can decrease pathological tau changes, including hyperphosphorylation, aggregation, and spreading, in mice with localized human wild-type tau (hTau) expression in the brain. We used adeno-associated viruses (AAVs) to express hTau locally in the entorhinal cortex of wild-type and GSK-3β hemi-knockout (GSK-3β-HK) mice. GSK-3β-HK mice had significantly less accumulation of hyperphosphorylated tau in synapses and showed a significant decrease of tau protein spread between neurons. In primary neuronal cultures from GSK-3β-HK mice, the aggregation of exogenous FTD-mutant tau was also significantly reduced. These results show that a partial decrease of GSK-3β significantly represses tau-initiated neurodegenerative changes in the brain, and therefore is a promising therapeutic target for AD and other tauopathies.